The development assumptions of Botswana television : an assessment - Mmusi, Bishy (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2002)
This study researched a project to set up a national television service for Botswana to find out whether the service could be used for rural development generally, and in particular to assist the Ministry of Health to implement its health projects in the rural areas and including the fight against the AIDS disease. It reviews conceptions of development and also analyses various communication models that usefully inform the conceptualisation of a TV service that can contribute to development. The study was done by going through reports of feasibility studies on the project and through letters of official correspondence among officials of the Government of Botswana who debated the subject of whether or not the country should have a national TV service. The reports and correspondence were supplemented with interviews of key people involved in the implementation of the project, as well as interviews of officials of the Ministry of Health. The findings of the study are that the Botswana television service project started and ended on a footing that forgot about television, a medium that is dependent on professional and organisational capacity and purpose, and as a result the project did not take-off. A qualitative method was used as the study required in-depth interviews during which new issues kept on emerging and nothing could be pre-determined because the study took place as the project was being implemented. The study was completed in June 2000, at a point where the project should have been completed but it was discovered that the station could not go on air as a television service had not been conceptualised and there was no management structure in place and the Government of Botswana appealed to the British Government for the staff of the British Broadcasting Corporation to come quickly to Botswana to rescue the project and put it on track, supposedly. The study has concluded that the Botswana television service project became stillborn because there was a lack of professional and intellectual capacity to conceptualise the service, and instead there had been too much concentration on the construction of the TV building and acquisition of equipment.
Keywords: Television -- Social aspects -- Botswana; Botswana -- Social conditions; AIDS (Disease) -- Botswana